Relato de Experiência do Programa Residência Pedagógica - PIMENTA, Patrícia Yasmin Lima (2022)
This Course Conclusion Work has the structural configuration based on the Normative Instruction nº 01/2022 of the Dean of Undergraduate Studies of the Federal University of Pará, which establishes rules about the activities of the TCC, made more flexible due to the consequences of the COVID-19 pandemic. Having said this, the present report will present a synthesis of the actions carried out in 18 months of work in the first edition of the Pedagogical Residency Program, presenting the methodologies used in this period, with emphasis on the actions with the greatest formative emphasis for the scholarship holder. The didactic projects and teaching practices explained in the report are the methodologies that used technological tools to assist the chemistry classes at Pitágoras State High School, located in the city of Ananindeua, from 2018 to 2020. We will highlight didactic interventions using the Classroom and Google Forms platforms, to provide continuity in the classes in a remote format; YouTube, for students to have access to video lessons prepared by the residents; Instagram, used to work on the contents in the form of summaries, questions and; separate videos on some chemistry subjects. The result obtained from these projects was the great participation of students during the application and development of the methodologies, as well as the importance of this activity in the teaching training of the scholarship holder author of this report.